Effect of diagnosed sleep disorders on baseline concussion symptom, cognitive, and balance assessments in collegiate athletes - McAllister-Deitrick, J.; Trbovich, A. M.; Broglio, S. P.; McCrea, M.; McAllister, T. W.; Kontos, A. P. (The American Journal of Sports Medicine, 2020)
Background: Symptoms, cognition, balance, and other domains are commonly assessed at baseline testing as part of comprehensive preseason evaluations among collegiate student-athletes. Although approximately 27% of college students have at least 1 sleep disorder, researchers have yet to examine the role of a preexisting sleep disorder on preinjury baseline performance. Purpose: To compare athletes with and without a reported history of diagnosed sleep disorders on commonly used baseline concussion assessments. Study Design: Cross-sectional study; Level of evidence, 3. Methods: A total of 666 National Collegiate Athletic Association student-athletes completed baseline measures including the Balance Error Scoring System (BESS), Brief Symptom Inventory-18 (BSI-18), Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT), Post-Concussion Symptom Scale (PCSS), Sport Concussion Assessment Tool-5th Edition (SCAT5), and Standardized Assessment of Concussion (SAC). There were 333 athletes with a history of diagnosed sleep disorders who were matched on age, sex, sport, and concussion history to 333 athletes with no history of diagnosed sleep disorders. Participants in both groups had a mean age of 19.89 ± 1.36 years and included 182 (54.7%) male athletes, and 126 (37.8%) reported a history of =1 concussions. Results: A series of 1-way analyses of covariance with Bonferroni corrections revealed significant group differences on the BESS (F1,559 = 8.88; P < .01); BSI-18 somatization (F1,640 = 18.48; P < .01), depression (F1,640 = 18.78; P < .01), anxiety (F1,640 = 19.42; P < .01), and global severity index (F1,640 = 27.18; P < .01); PCSS (F1,424 = 29.42; P < .01); SCAT5 symptom number (F1,634 = 28.79; P < .01) and symptom severity (F1,634 = 31.74; P < .01); and SAC (F1,578 = 4.36; P = .037). Specifically, while the sleep disorder group did perform better on the BESS, they also reported higher symptoms on the BSI-18, PCSS, and SCAT5 and performed worse on the SAC. There were no group differences on ImPACT performance. Conclusion: Collegiate student-athletes with diagnosed sleep disorders reported elevated affective and concussion symptoms at baseline that could affect the interpretation of postinjury impairments and symptoms. Based on the small effect sizes of our findings, however, the magnitude of these differences is of questionable clinical significance. Still, clinicians should consider diagnosed sleep disorders as reported during preparticipation sports physical examinations when interpreting baseline and postinjury concussion assessments.